2013
DOI: 10.2147/cia.s45064
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SIRT1 combined with gemcitabine therapy for pancreatic carcinoma

Abstract: BackgroundPancreatic carcinoma possesses one of the highest lethality rates, highest drug-resistance, and highest incidence rates. The objective of this research was to enhance the efficacy and drug-resistance for pancreatic carcinoma by using inhibition of SIRT1 combined with gemcitabine therapy methods.MethodsThree pancreatic carcinoma cells (PANC-1 cells, BxPC-3 cells, and SW1990 cells) received treatment with physiological saline, inhibition of SIRT1, gemcitabine, and combination therapy with inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
7
2
Order By: Relevance
“…Tumor xenografts were treated with vehicle, G-1 at 0.5 mg/kg/day alone and in combination with Sirtinol at 10 mg/kg/day. 32 , 33 , 34 These administrations were well tolerated as no change in body weight or in food and water consumption was observed together with no evidence of reduced motor function. No significant difference in the mean weights or histologic features of the major organs (liver, lung, spleen and kidney) was also detected after killing among vehicle and ligand-treated mice, thus indicating a lack of toxic effects.…”
Section: Resultsmentioning
confidence: 97%
“…Tumor xenografts were treated with vehicle, G-1 at 0.5 mg/kg/day alone and in combination with Sirtinol at 10 mg/kg/day. 32 , 33 , 34 These administrations were well tolerated as no change in body weight or in food and water consumption was observed together with no evidence of reduced motor function. No significant difference in the mean weights or histologic features of the major organs (liver, lung, spleen and kidney) was also detected after killing among vehicle and ligand-treated mice, thus indicating a lack of toxic effects.…”
Section: Resultsmentioning
confidence: 97%
“…6D) were observed as UES in PharmacoDB, of which FOXJ1 underexpression is a marker of poor prognosis in gastric cancer [133], reduced expression of FOXG1 is correlated with worse prognosis in breast cancer [134], FOXJ3 is inhibited by miR-517a and associated with lung and colorectal cancer cell proliferation and invasion [135,136], and FOXH1 is overexpressed in breast cancer, and FOXH1 inhibition reduces proliferation in breast cancer cell lines [137]. Although not UES in PharmacoDB, inhibition of the HST1 homolog, SIRT1, by Tenovin-6 inhibits the growth of acute lymphoblastic leukemia cells and enhances cytarabine cytotoxicity [138], enhances gemcitabine efficacy in pancreatic cancer cell lines, and improves survival in a pancreatic cancer mouse model [139]. Thus, loss of this gene module that positively regulates DNA replication initiation appears to be robustly involved in oncogenesis and is also synthetic lethal with gemcitabine and cytarabine.…”
Section: Resultsmentioning
confidence: 99%
“…However, SIRT1 inhibition in vivo was found to promote pancreatic cancer xenograft tumor growth [ 52 ]. In addition, SIRT1 has been shown to facilitate pancreatic cancer chemoresistance, while application of a combination therapy consisting of a SIRT1 inhibitor and gemcitabine has been shown to have enhanced efficacy for pancreatic cancer [ 53 , 54 ]. Here, we found that SIRT1 was highly expressed in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%